Improving Federal and Department of Defense Use of Service-Disabled Veteran-Owned Businesses - Cox, Amy G. (RAND Corporation, 2013)
The report investigates the barriers that service-disabled veteran-owned small businesses (SDVOSBs) may face when attempting to contract with the federal government and the Department of Defense. The government and DoD goals are to award 3 percent of prime-contract dollars to SDVOSBs but current contracting falls below that level.